Invasive fungal disease in COVID-19 patients: a single-center prospective observational study - Adzic-Vukicevic, Tatjana; Mladenovic, Milos; Jovanovic, Snezana; Soldatović, Ivan; Radovanovic-Spurnic, Aleksandra (Frontiers in Medicine, 2023)
Background Invasive fungal diseases (IFDs) are caused by fungal infections that manifest as serious secondary infections in patients with COVID-19. The increased morbidity and mortality rates are most frequently observed in patients with COVID-19-associated pulmonary aspergillosis (CAPA) and COVID-19-associated candidiasis (CAC). CAPA is the most frequently encountered infection with an incidence rate of 0.7–7.7%, while CAC is a less common and less studied fungal infection in COVID-19 patients. Materials and methods The present article is a prospective observational single-center study that was conducted between 1 September 2021 and 24 December 2021, involving 6,335 patients who were admitted to COVID Hospital “Batajnica,” University Clinical Center of Serbia, Belgrade. Results Of the 6,335 patients hospitalized during the four-month period of the study, 120 patients (1.86%) who had a proven diagnosis of IFD were included in the study. These patients were divided into two groups: CAPA patients (n = 63) and CAC patients (n = 56); however, one of the 120 patients was diagnosed with Cryptoccocus neoformans infection. The mean age of the study population was 65.7 ± 13.9 years, and 78 (65.5%) of them were men. The patients were identified to have the following non-malignant comorbidities: arterial hypertension in 62 (52.1%) patients, diabetes mellitus in 34 (28.65), pre-existing lung damage similar to that observed in COPD and asthma in 20 (16.8%), and chronic renal insufficiency in 13 (10.9%) patients. The hematological malignancies were found to be the most prevalent malignancies and were identified in 20 (16.8%) patients, particularly in CAPA patients [11 (17.5%); p < 0.041]. Fiberoptic bronchoscopy with bronchoalveolar lavage fluid (BALF) and microscopic examination confirmed the presence of fungal infections in 17 (14.3%) patients. Serology testing was also performed in the majority of cases. Antibodies against Aspergillus spp. and Candida spp. were predominantly found in CAPA patients (p < 0.001). The patients were also tested for the presence of (1–3)-β-D glucan (p < 0.019), galactomannan, and mannan in the specimens. Blood cultures were found to be positive in 45 (37.8%) patients, mostly in CAC patients. Mechanical ventilation was applied in 41 (34.5%) patients, while a non-invasive technique, such as continuous positive airway pressure (CPAP) or high-flow nasal cannula (HFNC), was used in 20 (16.8%) patients. The following antifungals were administered: echinocandins in 42 (35.3%), voriconazole in 30 (25.2%), and fluconazole in 27 (22.7%) patients. Most of the patients received systemic corticosteroids (mainly methylprednisolone), while 11 (9.16%) received favipiravir, 32 (26.67%) remdesivir, 8 (6.67%) casirivimab/imdevimab, and 5 (4.16%) sotrovimab. The outcome was lethal in 76 (63.9%) patients, predominantly CAC patients (p < 0.001). Conclusion Invasive fungal disease is a severe complication associated with COVID-19 and accounts for increased mortality in these patients. Early identification and appropriate treatment may provide a favorable outcome.